1983
DOI: 10.1111/j.1524-4725.1983.tb00883.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemosurgical Reports: Perineural Spread of Basal‐Cell Carcinoma

Abstract: Basal-cell carcinoma with perineural invasion is a rare occurrence. Ten patients with this phenomenon are described. Review of our cases and cases in the literature indicates that perineural spread of basal-cell carcinoma is most common in men with recurrent tumors. The horizontally cut frozen sections that are utilized in Mohs surgery maximize the chances of discovering basal-cell carcinoma with undiagnosed involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0
3

Year Published

1993
1993
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 13 publications
3
86
0
3
Order By: Relevance
“…He also continued previous work by Mohs and Lathrop 2 and showed that tumor cells spread along a plane of least resistance in the perineural space between the nerve fiber and its sheath. This space extends from the smallest peripheral nerve branches to the central subarachnoid space and allows access to the central nervous system (CNS) by cutaneous malignancies 3 of the head and neck. "Invading" tumor cells tend to be localized to the nerve periphery, at the perineurium and endoneurium, generally without much invasion of the nerve fiber proper.…”
Section: Conclusion Previous Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…He also continued previous work by Mohs and Lathrop 2 and showed that tumor cells spread along a plane of least resistance in the perineural space between the nerve fiber and its sheath. This space extends from the smallest peripheral nerve branches to the central subarachnoid space and allows access to the central nervous system (CNS) by cutaneous malignancies 3 of the head and neck. "Invading" tumor cells tend to be localized to the nerve periphery, at the perineurium and endoneurium, generally without much invasion of the nerve fiber proper.…”
Section: Conclusion Previous Reportsmentioning
confidence: 99%
“…8 In the modern era, identification of PNI is facilitated by the horizontally cut frozen sections from Mohs micrographic surgery. 2,3 The chronicity of PNS displays considerable variation. McNab et al 9 reported a series of 21 patients with PNS of cutaneous squamous cell carcinoma (SCC) via the orbit.…”
Section: Conclusion Previous Reportsmentioning
confidence: 99%
“…Clinical borders often are more difficult to estimate (8). Furthermore, recurrent tumors tend to adopt a more aggressive histology than seen in the original tumor (8), and perineural invasion is most common in recurrent tumors (16). For these reasons, treatment is difficult.…”
Section: Recurrent Tumorsmentioning
confidence: 99%
“…A multidisciplinary approach often is the best means of management for the remaining tumors that are difficult because of size, location, histology, perineural invasion, recurrence, or host factors. In a review of basal cell carcinomas with perineural spread, Hanke et al (16) noted that Mohs surgery alone or in combination with major surgical resection and postoperative radiation was necessary to prevent further recurrences, especially in more advanced cases of neural involvement.…”
Section: Management Of Difficult Skin Cancersmentioning
confidence: 99%
“…145 Many studies that report skip lesions are earlier case series treated by MMS. [145][146][147][148][149][150] Matorin acknowledged the specific limitations of MMS to assess PNI due to technical processing and surgical access difficulties, and this is especially pertinent in cases of clinical PNI. 143 The existence of perineural space lymphatics has been discounted, and the skip lesion has never been proven histologically and most likely reflects artefact from histological processing 35,59,143 Panizza et al assessed the histopathological features of 51 specimens of cranial nerve involved with perineural spread from 49 patients.…”
Section: Immunosuppression and Sccmentioning
confidence: 99%